Multi-Level Influences on Physical Exercise Behavior of High School Students: A Social Ecological Approach - Tan Jie (Ilmu Inovasi Nusantara, 2024)
This study, based on the social ecological model, investigates the multifaceted factors influencing the physical exercise behavior of senior high school students through an extensive literature review and logical analysis, and subsequently offers targeted recommendations. The findings reveal that high school students' physical activity is shaped by a complex interplay of influences across several levels. At the individual level, factors such as gender and physical health are significantly associated with exercise behavior. Males tend to be more active than females, and students in better physical health are more likely to engage in regular physical activity. Family dynamics also play a crucial role. Support and encouragement from family members, particularly parents, greatly enhance students' likelihood of participating in sports and other physical activities. When families prioritize and value physical exercise, students are more inclined to adopt similar behaviors. The school environment further contributes to shaping exercise habits. The presence of adequate sports facilities and comprehensive physical education programs within schools are positively correlated with higher levels of student participation in physical exercise. Schools that invest in well-maintained sports infrastructure and offer diverse physical education curricula create conducive environments for students to be active. Social factors are equally influential. Peer participation in sports activities serves as a strong motivator for students. When peers are actively involved in sports, students are more likely to join in due to social bonding and peer pressure. Competitive pressure, while sometimes a source of stress, can also drive students to participate more in physical activities to excel and fit in socially. Based on these insights, the study suggests a multi-level intervention approach. Strengthening family support systems, improving school sports facilities, and fostering a supportive social environment are critical. These measures aim to promote healthier and more active lifestyles among high school students, addressing the issue from multiple angles to ensure a comprehensive and effective strategy